Varicella gangrenosa with probable staphylococcal sepsis - Biswal, Niranjan; Kavirayani, Akhila Murthy; Parameswaran, Narayanan (Journal of Pediatric Infectious Diseases, 2006)
Sepsis is a rare complication following chickenpox in healthy children. Gangrene at different sites even in the absence of disseminated intravascular coagulation can result in high morbidity and mortality. Coagulase negative staphylococcus can rarely complicate in systemic sepsis and is probably a predictor of bad prognosis. Secondary skin infection following rupture of bullae requires prompt antibiotic therapy covering Streptococcus and Staphylococcus.
Keywords: Varicella; gangrene; sepsis; coagulase negative staphylococcus